HUBUNGAN ANTARA PERSEPSI SISWA TENTANG KEADAAN LINGKUNGAN FISIK SEKOLAH DENGAN MOTIVASI BELAJAR - Sona Idola; Afrizal Sano; khairani Khairani (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2016)
The school environment is a factor that affects student learning. School environment was created, well laid out for the benefit of the students as well. Phenomenon that occurs, some students found the state of the school environment is not good, the sound of passing vehicles, the complete lack of facilities and infrastructure so that motivate learning impaired. This study examines the relationship between students perceptions about the state of the school environment with learning motivation. This research study considered quantitative correlation type. Samples were SMP Pembangunan Laboratorium UNP Padang Students. Based on the results of the study there is a significant relationship between students' perceptions about the state of the school environment with learning motivation.